(untitled) (Swiss Medical Weekly, 2020)
In October 2019, a Swiss panel of experts met for the Dementia Summit in Brunnen, Switzerland, to discuss the latest scientific findings on basic and clinical research, as well as practical and political approaches to the challenges of dementia disorders in Switzerland. Here, we present the conference summary. To study pathophysiological changes, as well as the underlying mechanism of fluid biomarker changes, excellent experimental approaches, including transgenic mouse models, are available. Current knowledge about presymptomatic disease progression is largely derived from the longitudinal study of individuals with autosomal dominant mutations (Dominantly Inherited Alzheimer Network). Importantly, more than one third of identified dementia risk factors can be modified. For example, sleep disturbances are not only associated with dementia and neurodegeneration in specific brain regions, but also precede cognitive decline and contribute to the development of brain pathology. Regarding the neuropsychological examination of dementia disorders, standardised tests of social cognition, one of the six cognitive domains that must be assessed according to the fifth edition of the Diagnostic and Statistical Manual for Mental Disorders, are missing, but now under development. The most important new therapeutic approach in the treatment of Alzheimer’s disease is the current attempt to prevent β-amyloid accumulation. While until now clinical studies have failed because of side effects or insufficient clinical effectiveness, Biogen recently announced positive results of high doses of aducanumab, a monoclonal antibody against β-amyloid. Other approaches also show promise. In China, sodium oligomannate has been approved to treat Alzheimer’s disease. The substance suppresses gut bacterial amino acids-shaped neuroinflammation to inhibit Alzheimer’s disease progression. Assistive technologies for dementia patients can help identify relevant information for care and nursing, as well as measurements for clinical interventions. Dementia patients have a high risk of developing delirium, even in the home environment. Therefore, it is necessary to use and further develop multi-disciplinary and systematic detection and prevention strategies. Homecare models for dementia patients with multidisciplinary teams have been established and evaluated and should be expanded. Dementia is the third-leading cause of death in Switzerland. In palliative care for severe dementia, the improvement of quality of life is of primary importance. The goals of the National Dementia Strategy, to increase the quality of life in those affected and to reduce taboos surrounding the disease, are still unrealised. The need for further national and regional engagement in order to implement the different findings of the strategy has largely been acknowledged, and these implementations have become the core tasks of a national dementia platform.